Informal Capital Market and Environmental Factors in Nigeria - Oluwafemi, ADEUSI Stephen; Adesola, OGUNMAKIN Adeduro (Asian Economic and Financial Review, 2014)
Our environments are closely instutionalized with collections of human and material resources for the purpose of economic production and profitability. It was based on this premise that, this study sought to examine the effect of environmental factors on informal capital market in Nigeria. In doing this, Chi-square method was employed. The result revealed the existence of a significant relationship between the environmental factors and the informal capital market performances. The study therefore recommended that the operators of the informal capital market should be accorded the safety of their deposit and a high profitability should be given a priority in other to enhance the performances of the market.